Errata: Communications - Scientific Letters of the University of Zilina, Vol. 20, No.2, 2018, ``Application of a Priori and a Posteriori Estimate on Risk Assessment'', pp. 56-61. The proper name of third author should be as follows: Witalis Pellowski. - Sivakova, Lenka; Zubkova, Anna; Pellowski, Witalis (Communications - Scientific Letters of the University of Zilina, 2018)
Errata: Communications - Scientific Letters of the University of Zilina, Vol. 20, No.2, 2018, ``Application of a Priori and a Posteriori Estimate on Risk Assessment'', pp. 56-61. The proper name of third author should be as follows:Witalis Pellowski.
Keywords: Errata: Communications - Scientific Letters of the University of Zilina; Vol. 20; No.2; 2018; ``Application of a Priori and a Posteriori Estimate on Risk Assessment''; pp. 56-61. The proper name of third author should be as follows: Witalis Pellowski.